An interactive atlas for marine biodiversity conservation in the Coral Triangle - I. Asaad; I. Asaad; C. J. Lundquist; C. J. Lundquist; M. V. Erdmann; M. J. Costello (Earth System Science Data, 2019)
An online atlas of the Coral Triangle region of the Indo-Pacific biogeographic realm was developed. This online atlas consists of the three interlinked parts: (1) Biodiversity Features; (2) Areas of Importance for Biodiversity Conservation; (3) recommended priorities for Marine Protected Area (MPA) Network Expansion (http://www.marine.auckland.ac.nz/CTMAPS). The first map, Biodiversity Features, provides comprehensive data on the region's marine protected areas and biodiversity features, threats, and environmental characteristics. The second provides spatial information on areas of high biodiversity conservation values, while the third map shows priority areas for expanding the current Coral Triangle MPA network. This atlas provides the most comprehensive biodiversity datasets that have been assembled for the region. The datasets were retrieved and generated systematically from various open-access sources. To engage a wider audience and to raise participation in biodiversity conservation, the maps were designed as an interactive and online atlas. This atlas presents representative information to promote a better understanding of the key marine and coastal biodiversity characteristics of the region and enables the application of marine biodiversity informatics to support marine ecosystem-based management in the Coral Triangle region.